The relationship between reported coaching behaviours and learning resources on youth rugby players' attitudes towards injury prevention and performance in the tackle - Garnett, Daniel (Division of Exercise Science and Sports Medicine, 2019)
Background: Involvement in sports has numerous well-documented physiological and psychological benefits but also carries a risk of injury. Due to the contact nature of Rugby, involvement in the game carries a greater risk of injury compared to other sports. The tackle phase of the game has resulted in the most number of injuries in all levels of the game. Coaches are key elements in developing players and implementing injury prevention programmes. Certain coach behaviours may influence a player’s attitude, in turn the player’s behaviours, when implementing tackle techniques during training sessions and matches. Player behaviour has previously been identified as a risk factor for sustaining, or causing, an injury during a tackle. Objective: To examine the relationship between reported coaching behaviours and learning resources on players’ attitudes and behaviours towards injury prevention and performance in the rugby tackle. Methods: This cross-sectional survey used a questionnaire comprising a 5-point Likert scale to assess junior rugby players’ (n=164) attitudes (importance) and behaviours (frequency and quantity). The main outcome measurements were the relationships between reported tackle coaching methods and the players' tackle training attitudes and behaviours using the χ² test and Cramer's V. Results: Player-rated importance of injury prevention was positively correlated with verbal instruction from the coach to the individual player (29% somewhat important - very important, χ² (16)=30.41, p<0.05, Cramer's V=0.22, moderate) and to the entire team (34% somewhat important-very important, χ² (16)=34.05, p<0.01, Cramer's V=0.23, moderate). The more time spent by the coaches on teaching proper techniques to prevent injuries, the higher players rated the importance of injury prevention (28% somewhat important-very important, χ² (16)=29.13, p<0.05, Cramer's V=0.21, moderate). Training books as a learning resource was positively associated with how important players rated tackle injury prevention (27% somewhat important-very important/much-very much, χ² (16)=28.67, p<0.05, Cramer’s V=0.21, moderate) and performance (32% somewhat important-very important/much-very much, χ² (16)=27.22, p<0.05, Cramer’s V=0.21, moderate). Training videos, as a learning resource, was also positively associated with the importance of tackle performance (32% somewhat important-very important/much-very much, χ² (16)=27.22, p<0.05, Cramer’s V=0.21, moderate) but not injury prevention (39% somewhat important-very important/much-very much, χ² (16)=21.50, p<0.05, Cramer’s V=0.18, weak) Conclusions: This research reports on the association between reported coaching behaviours and learning resources on players’ attitudes and behaviours towards injury prevention and performance in the tackle in rugby. Reported coaching behaviours, which incorporated individual and team verbal instructions when teaching tackle techniques to prevent injuries, resulted in more risk adverse player attitudes towards injury prevention when performing the tackle skill in training and matches. When the goal was to improve tackle performance, more importance is given to training proper technique in the tackle when compared to the goal of preventing injury. Players identified training videos and training books as the most preferential learning resources for improving tackle performance. Training books were also identified as an important learning resource with regards to tackle-related injury prevention attitudes and should be explored further.